Analysis of History Teachers' Pedagogical Skills in Junior High School of MTs Al Khairaat Kalukubula - Dita Reskiani; Hasan; Windayanti; Fajar Nugroho (Kirana Publisher (KNPub), 2026)
This study aims to describe the pedagogical knowledge and skills of history teachers at MTs Al-Khairaat Kalukubula and identify factors that support and hinder their implementation. Pedagogical competence is a teacher's ability to understand students, design and implement learning, provide learning outcomes, and develop students' potential to achieve optimal learning objectives. This study used a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The research subjects included history teachers, the principal, and students at MTs Al-Khairaat Kalukubula. The results indicate that historical teachers understand student characteristics and systematically plan learning through tools such as syllabi, lesson plans, annual programs (Prota), and semester programs (Promes). Learning progressed quite well, despite challenges such as limited media, infrastructure, and limited teaching staff. Learning outcomes were evaluated through assignments, daily tests, mid-term exams, and remedial classes for students who have not yet met the Minimum Completion Criteria (KKM). In general, the pedagogical competence of history teachers at MTs Al-Khairaat Kalukubula has been quite good, demonstrated by their ability to manage educational, communicative, and reflective learning. However, improvements are needed in the areas of method variation, the use of digital learning media, and more optimal implementation time.